From Austen to DeepL: Women’s language translation in Sense and Sensibility - Purwaningsih, Dyah Raina (Universitas Mulawarman, 2026)
This paper aims to analyze the translation of women’s language features in Jane Austen’s novel Sense and Sensibility. The study focuses on understanding how the unique linguistic characteristics of female characters in the novel are rendered in the target language both by the official translator and by DeepL.The researchers are interested in cutting open the translation resulted by those two different translators. The study considers both the linguistic and cultural aspects of the translations, aiming to identify any potential challenges faced by translators in conveying the subtleties of women’s language features. The research used qualitative methods. Close reading and textual analysis were employed to identify and examine instances of women’s language features in the original text. Theoretically, the findings of this research shed light on the strategies employed by both the human translator and the DeepL in rendering women’s the language features. It is empirically proven that emphatic stress, lexical hedges/fillers, and intensifier are the most frequently used features in the novel. As for the translation strategies, the official human translator tends to employ a wider range of translation strategies than the DeepL.